THE INFLUENCE OF CORPORATE GOVERNANCE, RISK, AND COMPANY VALUE OF THE BANKING SECTOR ON THE INDONESIA STOCK EXCHANGE - Della Alfa'Atun; Aloisius Hama (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the effect of corporate governance, risk, and firm value in the general banking sector companies listed on the Indonesia Stock Exchange. The population in this study the population used is the general banking sector companies listed on the Indonesia Stock Exchange. The number of samples that will be used in this study are 40 banking companies. With the time period used is 3 years, the number of observation data (n) used is 120 data. The analytical technique used in this study is analysis using the path analysis method. The path analysis method in this study is used to estimate the causal relationship between the variables in the study. The results of the study show that corporate governance contributes to firm value in general banking sector companies listed on the Indonesia Stock Exchange. Corporate governance contributes to the risk of general banking sector companies listed on the Indonesia Stock Exchange. Risk does not contribute to firm value in general banking sector companies listed on the Indonesia Stock Exchange. The direct influence of corporate governance on firm value in general banking sector companies listed on the Indonesia Stock Exchange.